Perancangan Sistem Monitoring Jadwal Bus TransPalu Sebagai Solusi E-Government Untuk Meningkatkan Layanan Publik - Muthiah Azzahrah; Andi Hendra (IDEALIS : InDonEsiA journaL Information System, 2026)
Public transportation services in Palu City have adopted digital features through Sangu Palu and Mitra Darat, but still face unstable GPS data, weak real-time notifications, limited local data control, and fragmented coordination between government and field personnel. This study aims to design a Trans Palu bus schedule monitoring system that provides real-time passenger information and strengthens local e-government transport governance. Design Science Research was used. Data were collected through interviews with agencies and bus officers, field observations, user surveys, literature review, and system analysis. The artifact is a multilayer software architecture with four modules: passenger, administrator, operator, and field officer. The design focuses on the passenger and administrator modules, while the operator and field officer modules are formulated conceptually to support data recording and operational integration. A survey of 67 respondents identified schedules, estimated arrival times, real-time bus positions, nearest stops, fastest routes, and notifications as user priorities. The artifact includes route and schedule management, fleet monitoring, estimated arrival times, a journey planner, incident reporting, dashboard analytics, and role-based access. Evaluation yielded a model consistency score of 3.65, a technical feasibility score of 3.0, and an expert validation score of 3.96, indicating that the design is feasible with improvements. This study contributes an architectural foundation for local governments to develop locally grounded public transport monitoring systems. Its novelty lies in integrating passengers, local-government administrators, operators, and field officers in one ecosystem combining passenger information services with oversight, operational management, and local data control.